Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the solution by substitution.

Y= —5x + 13
-6x + 6y = 6

Show/ explain your work


Sagot :

Answer:

the solution is (2, 3)

Step-by-step explanation:

Make this work easier by reducing the second equation:

-x + y = 1, or y = x + 1

Substititing x + 1 for y in the first equation, we get:

x + 1 = -5x + 13, or (after combining like terms):

6x = 12

Then x = 2, and bercause y = x + 1 (see above), y = 2 + 1 = 3

Then the solution is (2, 3)